Overview of Ethnobotanical-Pharmacological Studies Carried Out on Medicinal Plants from the Serra da Estrela Natural Park: Focus on Their Antidiabetic Potential - Radhia Aitfella Lahlou; Filomena Carvalho; Maria João Pereira; João Lopes; Luís R. Silva (MDPI AG, 2024)
The Serra da Estrela Natural Park (NPSE) in Portugal stands out as a well-preserved region abundant in medicinal plants, particularly known for their pharmaceutical applications in diabetes prevention and treatment. This comprehensive review explores these plants' botanical diversity, traditional uses, pharmacological applications, and chemical composition. The NPSE boast a rich diversity with 138 medicinal plants across 55 families identified as traditionally and pharmacologically used against diabetes globally. Notably, the Asteraceae and Lamiaceae families are prevalent in antidiabetic applications. In vitro studies have revealed their significant inhibition of carbohydrate-metabolizing enzymes, and certain plant co-products regulate genes involved in carbohydrate metabolism and insulin secretion. In vivo trials have demonstrated antidiabetic effects, including glycaemia regulation, insulin secretion, antioxidant activity, and lipid profile modulation. Medicinal plants in NPSE exhibit various activities beyond antidiabetic, such as antioxidant, anti-inflammatory, antibacterial, anti-cancer, and more. Chemical analyses have identified over fifty compounds like phenolic acids, flavonoids, terpenoids, and polysaccharides responsible for their efficacy against diabetes. These findings underscore the potential of NPSE medicinal plants as antidiabetic candidates, urging further research to develop effective plant-based antidiabetic drugs, beverages, and supplements.